Use of the FM Systems for the Auditory and Speech Perception Improvements in Children with ASD. Pilot Study - U.A. Mamokhina; K.A. Fadeev; D.E. Goyaeva; A.A. Ilyunceva; T.M. Ovsyannikova; T.S. Obukhova; K.R. Salimova; A.M. Rytikova; D.V. Davydov (Клиническая и специальная психология)
Objectives. Children with Autism Spectrum Disorder (ASD) often face difficulties in speech perception, particularly in noisy environments. These problems are associated with central auditory processing disorders. FM systems, which improve the signal-to-noise ratio, can be used to enhance speech perception. The aim of this study was to investigate the effects of FM systems when working with children with ASD in noisy conditions and their use in a school setting. Methods. The pilot study was conducted in two stages. In the first stage, the “Words in Noise” test and the “Sentence Repetition” task were used to assess children’s ability to recognize speech in noisy conditions with and without the use of FM systems. Fourteen children with ASD and 14 typically developing peers participated in the experiment. In the second stage, FM systems were studied in real school environments with 10 elementary school students with autism. Changes in auditory abilities were assessed using the L.I.F.E.-R scale. Results. In the first stage, it was found that children with ASD recognized significantly fewer words in noisy conditions compared to their typically developing peers. In the “Sentence Repetition” task, the use of FM systems improved the performance of children with ASD from 58.3% to 76.9% (p=0.0005). In the second stage, most participants showed minimal changes in auditory ability scores on the L.I.F.E.-R scale: the average score before using FM systems was 54.9, and after using them it was 57.4 (p=0.2322). However, several students showed improvements of 8–13 points, reflecting individual variability in the effect of using FM systems. Discussion. FM systems have demonstrated their effectiveness in improving speech perception in noisy environments for children with ASD. However, the integration of FM systems into the school process requires further research on their effectiveness in real conditions, as well as adaptations to minimize discomfort for children and improve interaction with teachers and tutors.